Extreme thermal load generation method for high-temperature structures in atmospheric environment - WANG Binwen; ZHANG Yi; QIN Qiang; CHEN Hong; WU Jingtao (Xibei Gongye Daxue Xuebao)
For addressing the severe aerodynamic thermal load simulation challenge of hypersonic aircraft in ground tests, an extreme thermal load generation method based graphite for high-temperature structures in atmospheric environment is proposed. Firstly, a thermal stress relief design method of graphite heating elements has been developed to ensure the integrity of graphite heating elements during high-power heating. Secondly, a method of creating closed transparent environment for graphite heating elements has been developed, with double-layer gas film cooling, which avoids severe oxidation of graphite heating elements in contact with oxygen at high temperatures and achieves the application of large heat flux loads in the atmospheric environment. Finally, a modular graphite ultra-high temperature heating device was developed based on the above method, and heating capacity tests were conducted on C/SiC test pieces in atmospheric environment. The research shows that the modular graphite ultra-high temperature heating device has the ultra-high temperature heating ability in atmospheric environments, with maximum radiation heat flux of 1.38 MW/m2, hot surface temperature of around 1 800 ℃, and the temperature rise rate can reach 40.3 ℃/s, providing technical conditions for the thermal test of hypersonic aircraft structure.